2021
DOI: 10.31539/costing.v4i2.1720
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Website Quality dan E–Satisfaction Terhadap E-Loyalty Pada Website pssi.org

Abstract: This study aims to acknowledge any relationship between Website Quality and E - Website user satisfaction with E-Loyalty of website users. In this study the authors used quantitative research methods. The independent variable is the variable that affects or causes the change or the dependent variable arises. In this research, the independent variables are Website Quality and E - Satisfaction. The dependent variable on the variable which is the result of the effect, because the independent variable. The depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…These results show that the second hypothesis which states that website quality has a significant positive effect on eloyalty is proven correct. These results are in line with the case researched by Supriadi & Yusuf (2021) which shows that website quality has a positive and significant effect on e-loyalty.…”
Section: The Effect Of Website Quality On E-loyaltysupporting
confidence: 91%
See 1 more Smart Citation
“…These results show that the second hypothesis which states that website quality has a significant positive effect on eloyalty is proven correct. These results are in line with the case researched by Supriadi & Yusuf (2021) which shows that website quality has a positive and significant effect on e-loyalty.…”
Section: The Effect Of Website Quality On E-loyaltysupporting
confidence: 91%
“…A real form of information technology is the service offered by a website. Web quality is measured by how customers can feel the service features and characteristics of the web meet their requirements and needs (Supriadi & Yusuf, 2021). E-Loyalty is defined as the desire to revisit a website with or without making online transactions (Suyono et al, 2020) The statistical results explain that website quality has a significant positive effect on e-loyalty.…”
Section: The Effect Of Website Quality On E-loyaltymentioning
confidence: 99%
“…Experiential value e mbraces entertainment, visual, escape, and interaction dimensions [83]. As Supriadi and Yusuf [84] and Leonnard [85] stated, the website's ease of use and flexibility establish trust and loyalty. Pandjaitan, et al [86]; Pham, et al [87] and Kamal, et al [88] revealed that designing an easy-to-understand website as perceived quality online creates consumer loyalty.…”
Section: Perceived Quality Online and Customerse-satisfactionmentioning
confidence: 99%